Determinants of Hand Washing with Soap (HWWS) in Rural Communities: Cross Sectional Study in Manggarai Regency East Nusa Tenggara Indonesia - Ngambut, Karolus; Banne Tondok, Santalia; Ata Maran, Albertus; Bare Telan, Albina; Rino Vanchapo, Antonius; R.V Purba, Ellen; Djunaedi, Djunaedi (International Journal of Health Sciences, 2023)
Hand Washing With Soap (HWWS) behavior is a simple thing that can be done to inhibit the transmission of disease from the source of infection. Not much is known with certainty about the determinants of community handwashing behavior as a basis for promoting handwashing behavior. The research aims to identify the various determinants of HWWS behavior in the rural community, the results of which can be considered for designing the promotion of HWWS behavior in rural community and economically vulnerable groups. A total of 52 villages as survey locations, interviews and observations were carried out on 168 household heads who were determined by purposive random sampling with the inclusion criteria of having toddlers, and the house is on the edge of a river / beach. Univariate data processing to describe the characteristics of respondents and bivariate analysis to describe the relationship between the various HWWS behavior variables. The results of the study showed that the majority of the community already had HWWS facilities and were around the house where they lived. Critical times for community hand washing behavior are when hands are dirty, after feeding livestock and before eating. There is no difference between the determinants of HWWS behavior with education and with household categories based on the number of repeaters. Health cadres and local health workers dominate the sources of information obtained by the community regarding HWWS behavior. The implication of the results of this study is that the promotion of HWWS behavior in the community needs to consider non-health messages such as HWWS carried out when hands are dirty, after feeding livestock and before eating. In addition to inhibiting the spread of diseases that are transmitted through hands, the goal of HWWS behavior is also. In addition, health cadres and health workers are very important as a channel for conveying education about HWWS behavior in the community, in addition to the use of social media.